Dynamic properties of tennis balls - Cross, R. (Sports Engineering, 1999)
Measurements are presented on the dynamic properties of several different tennis balls, during impacts on a force plate. The force on a tennis ball rises rapidly to about half its maximum value in the first 200 ms of the impact due to compression of the cloth cover and the rubber wall near the impact point. The wall then collapses inwards, resulting in a sudden decrease in ball stiffness. Results are presented on the force waveform, the impact duration, ball compression and coefficient of restitution as a function of ball speed.